Determinar los valores de hemoglobina glicosilada en pacientes diabéticos con insuficiencia renal crónica en tratamiento de diálisis del Hospital Teófilo Dávila de junio a septiembre del año 2013 - Amagua, Silvia (2014)
The objective of this study is to determine the level of haemoglobin in diabetic patients with CKD dialysis treatment Teófilo Dávila Hospital in the period from June to September 2013. Descriptive cross-sectional study.